An Eight-Membered Ring Molecular Framework Based on Carbazole for the Development of Electroluminescent Materials - An Yan; Shipan Xu; Xuyang Du; Chengyun Zhu; Shengli Li; Xiaolong Yang; Guijiang Zhou; Yuanhui Sun (Molecules)
The organic light-emitting diode (OLED) has been regarded as the most prominent product in the current market of organic electronics, which has attracted growing attention because of their applications in full-color displays and solid-state lighting. Organic materials that exhibit strong luminescence in the solid state constitute the core position of OLED. Extensive research efforts to probe the structure of organic luminescent materials have attracted considerable attention to the conjugated fusion ring architecture. This is because it can confer molecular rigidity and helps to inhibit intermolecular interactions and non-radiative transitions, thus enhancing the performance of luminescent materials. Here, we use an efficient and simple method to construct an eight-membered ring molecular framework based on carbazole. Moreover, we have introduced groups with different electron-withdrawing abilities to develop a series of luminescent molecules. The results show that the nonplanar structure based on the eight-membered ring suppresses fluorescence quenching caused by molecular aggregation. As the doping concentration increases, the electroluminescence spectrum remains basically unchanged, indicating that the eight-membered ring structure can effectively suppress the intermolecular interaction. Notably, DCBz-pm exhibits deep blue emission with a Commission Internationale de l’Eclairage (CIE) coordinate of (0.158, 0.046), which nearly meets the BT. 2020 standards. The DCBz-CN device reaches a maximum external quantum efficiency (EQE) of 4.36%. These results offer a new design strategy for improving the performance of OLEDs.